Hypercapnia attenuates ventilator‐induced lung injury via a disintegrin and metalloprotease‐17. (5th September 2014) - Otulakowski, Gail; Engelberts, Doreen; Gusarova, Galina A.; Bhattacharya, Jahar; Post, Martin; Kavanagh, Brian P.
Key points Hypercapnia is common in mechanically ventilated patients with lung injury; while CO2 can ameliorate experimental lung injury, it can also cause harm. Because hypercapnia can protect against ventilator‐induced lung injury (VILI), understanding its impact on key signalling pathways may provide insight into the mechanisms of VILI. We show that hypercapnia blocks stretch‐mediated activation of p44/42 mitogen‐activated protein kinase (MAPK) signalling in alveolar epithelial cells; this occurs through inhibition of sheddase (i.e. the metalloprotease, ADAM17), which releases ligands that bind to the epidermal growth factor receptor. In vivo pharmacological blockade of ADAM17 reduces downstream MAPK activation and attenuates VILI in a two‐hit mouse model. Thus, hypercapnia uncovered a novel ADAM17‐dependent mechanism of VILI, and this represents a potential therapeutic target. Abstract Hypercapnic acidosis, common in mechanically ventilated patients, has been reported to exert both beneficial and harmful effects in models of lung injury. Understanding its effects at the molecular level may provide insight into mechanisms of injury and protection. The aim of this study was to establish the effects of hypercapnic acidosis on mitogen‐activated protein kinase (MAPK) activation, and determine the relevant signalling pathways. p44/42 MAPK activation in a murine model of ventilator‐induced lung injury (VILI) correlated with injury and was reduced in hypercapnia. When cultured rat alveolar epithelial cells were subjected to cyclic stretch, activation of p44/42 MAPK was dependent on epidermal growth factor receptor (EGFR) activity and on shedding of EGFR ligands; exposure to 12% CO2 without additional buffering blocked ligand shedding, as well as EGFR and p44/42 MAPK activation. The EGFR ligands are known substrates of the matrix metalloprotease ADAM17, suggesting stretch activates and hypercapnic acidosis blocks stretch‐mediated activation of ADAM17. This was corroborated in the isolated perfused mouse lung, where elevated CO2 also inhibited stretch‐activated shedding of the ADAM17 substrate TNFR1 from airway epithelial cells. Finally, in vivo confirmation was obtained in a two‐hit murine model of VILI where pharmacological inhibition of ADAM17 reduced both injury and p44/42 MAPK activation. Thus, ADAM17 is an important proximal mediator of VILI; its inhibition is one mechanism of hypercapnic protection and may be a target for clinical therapy.